Immune response modulation using Tolfenamic acid as an effective therapeutic for Burkholderia pseudomallei infection - Wilson, William J., author; Hanneman, William, advisor; Slayden, Richard, committee member; Legare, Marie, committee member; Tjalkens, Ronald, committee member (Colorado State University. Libraries, 2016)
Melioidosis is a tropical, often fatal, disease caused by the aerobic, Gram-negative facultative intracellular bacterium Burkholderia pseudomallei. Despite its growing global burden and high fatality rate, little is known about the disease. Recent studies demonstrate that Cyclooxygenase-2 (COX-2) inhibition is an effective post-exposure therapeutic to pulmonary melioidosis by inhibiting the production of Prostaglandin E2 (PGE2). However, this effective treatment was conducted using an experimental COX-2 inhibitor which is not approved for human or animal use, therefore, an alternative COX-2 inhibitor needs to be identified for further studies. Tolfenamic acid (TA) is a non-steroidal anti-inflammatory drug (NSAID) developed for COX-2 inhibition and is marketed outside of the United States for the treatment of migraines. While this drug was developed for COX-2 inhibition, it has been found to modulate other aspects of inflammation. In this study, we analyzed the effect of TA on cell survival, regulation of COX-2 and Nuclear factor- kappaB (NF-ĸB) protein expression as well as PGE2 production using RAW 264.7 cells infected with B. pseudomallei. We used this information to develop a protocol to evaluate the effectiveness of post-exposure treatment with TA as a therapeutic and compared these results to effective Ceftazidime treatments and the co-treatment of TA with a sub-therapeutic treatment of Ceftazidime in BALB/c mice. TA effectively increased cell viability in vitro and was able to reduce COX-2 expression and PGE2 production while also decreasing NF-ĸB activation during infection. Oral administration of TA to BALB/c mice infected with B. pseudomallei was able to significantly increase survival outcome, however, this did not alter bacterial load or dissemination within organ tissues. The co-treatment of TA with a sub-therapeutic treatment of Ceftazidime was able to substantially increase survival outcome and clear the bacterial load within organ tissue. We demonstrate that post-exposure treatment with TA and sub-therapeutic Ceftazidime is effective to treat melioidosis in BALB/c mice. Additionally, we further elucidate the inflammatory response to B. pseudomallei.